2017
DOI: 10.11138/gchir/2017.38.1.033
|View full text |Cite
|
Sign up to set email alerts
|

Deep sternal wound infections: a severe complication after cardiac surgery

Abstract: Sternal Wound Infections (SWI) represent a dangerous complication after cardiac surgery entailing significantly longer hospital stays and worse short-term survival, especially in case of deep infections (DSWI) with the onset of osteomielitis or mediastinitis. In the literature, the real incidence of SWI 1 is estimated between 0.25% and 10%, while we can gain an insight into the prognostic impact of mediastinitis thinking about the high mortality rate between 14-47% related to this complication, that usually pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 3 publications
1
11
0
1
Order By: Relevance
“…18 Since then, it was shown that this method improved blood perfusion of the wound edges' and accelerated granulation and wound healing, leading to earlier treatment of DWSI and better survival. 2,19 In the present study, DWSI was associated with a higher early inhospital (within 30 days) and 1-year mortality. Similarly, a significantly higher 30-day and 1-year mortality were reported in patients with DWSI compared with those without DWSI by Cayci et al 20 and Sears et al, 5 respectively.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…18 Since then, it was shown that this method improved blood perfusion of the wound edges' and accelerated granulation and wound healing, leading to earlier treatment of DWSI and better survival. 2,19 In the present study, DWSI was associated with a higher early inhospital (within 30 days) and 1-year mortality. Similarly, a significantly higher 30-day and 1-year mortality were reported in patients with DWSI compared with those without DWSI by Cayci et al 20 and Sears et al, 5 respectively.…”
Section: Discussionsupporting
confidence: 47%
“…After the formation of sufficient granulation and two sterile culture from the mediastinum, the sternum is closed as usual, with or without tissue flaps . Since then, it was shown that this method improved blood perfusion of the wound edges’ and accelerated granulation and wound healing, leading to earlier treatment of DWSI and better survival …”
Section: Discussionmentioning
confidence: 99%
“…The most common pathogens detected in DSWI are Staphylococcus aureus , especially methicillin‐resistant species, followed by Gram‐negative as Pseudomonas aeruginosa , Klesbiella Pneumoniae , or Enterobacter spp. with increasing incidence and multidrug resistance …”
Section: Introductionmentioning
confidence: 99%
“…Post-operative infection in cardiac surgery patients has been linked to patient outcome [10]. Nosocomial pneumonia, surgical site infection, mediastinitis, bacteremia, and sepsis are common infectious processes that can affect outcome [11].…”
Section: Introductionmentioning
confidence: 99%